Sistem Penentuan Produksi Makanan Pada Warung Sate Madura Malengkeri Menggunakan Fuzzy Logic Metode Tsukamoto - Mutia Amatullah; Sumarnie; Andi Afrah Tenriajeng (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2024)
The production determination system using the Tsukamoto fuzzy method can be used to determine the optimum quantity in satay production. However, if the quantity of products produced by Warung Sate Madura Malengkeri is less than the customer demand, the eatery will miss the opportunity to maximize profits, and vice versa. Therefore, planning the production quantity in Warung Sate Madura Malengkeri is crucial to meet customer demand with the appropriate quantity.